Modulation of functional pendant chains within poly(ethylene glycol) hydrogels for refined control of protein release - Kim, Mirae (Sci Rep, 2018)
Hydrogels are highly attractive delivery vehicles for therapeutic proteins. Their innate biocompatibility, hydrophilicity and aqueous permeability allow stable encapsulation and release of proteins. The release rates also can be controlled simply by altering the crosslinking density of the polymeric network. However, the crosslinking density also influences the mechanical properties of hydrogels, generally opposite to the permeability. In addition, the release of larger proteins may be hindered below critically diminished porosity determined by the crosslinking density. Herein, the physical properties of the hydrogels are tuned by presenting functional pendant chains, independent of crosslinking density. Heterobifunctional poly(ethylene glycol) monomethacrylate (PEGMA) with various end functional groups is synthesized and copolymerized with PEG dimethacrylate (PEGDA) to engineer PEG hydrogels with pendant PEG chains. The pendant chains of the PEG hydrogels consisting of sulfonate, trimethylammonium chloride, and phenyl groups are utilized to provide negative charge, positive charge and hydrophobicity, respectively, to the hydrogels. The release rates of proteins with different isoelectric points are controlled in a wide range by the type and the density of functional pendant chains via electrostatic and hydrophobic interactions.